2014
DOI: 10.1534/genetics.114.170563
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Variation, Aneuploidy, and Nongenetic Mechanisms Suppress a Monogenic Trait in Yeast

Abstract: Clinically relevant features of monogenic diseases, including severity of symptoms and age of onset, can vary widely in response to environmental differences as well as to the presence of genetic modifiers affecting the trait’s penetrance and expressivity. While a better understanding of modifier loci could lead to treatments for Mendelian diseases, the rarity of individuals harboring both a disease-causing allele and a modifying genotype hinders their study in human populations. We examined the genetic archit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 88 publications
2
13
0
Order By: Relevance
“…GuHCl resistance might be caused by increased level of Hal3p (Sis2p) reported earlier [28] or also by some gene located on chromosome II. Emergence of aneuploid clones in response to a stressful condition is similar to other reported cases such as chromosome III amplification in response to heat stress or chromosome V amplification as an adaptation to high pH [17] as well as chromosome XIII disomy making gal7 strains galactose tolerant [29]. Interestingly, chromosome II disomy has been already described in some laboratory strains as a compensatory mechanism.…”
Section: Discussionsupporting
confidence: 81%
“…GuHCl resistance might be caused by increased level of Hal3p (Sis2p) reported earlier [28] or also by some gene located on chromosome II. Emergence of aneuploid clones in response to a stressful condition is similar to other reported cases such as chromosome III amplification in response to heat stress or chromosome V amplification as an adaptation to high pH [17] as well as chromosome XIII disomy making gal7 strains galactose tolerant [29]. Interestingly, chromosome II disomy has been already described in some laboratory strains as a compensatory mechanism.…”
Section: Discussionsupporting
confidence: 81%
“…In rare cases, these knockout strains may evolve resistance. An analysis of 247 genomes of these haploid galactose-resistant strains showed that 124 (~50%) were aneuploid, with an extra Chr XIII in 93 strains (75% of the aneuploid strains; Sirr et al, 2015). A gene on Chr XIII (GAL80) was linked with this resistance.…”
Section: Toxic Stressmentioning
confidence: 99%
“…Basic genetic analysis methods therefore fail to characterize the underlying genetic network, and efforts to optimize one of these traits traditionally rely on adaptive evolution or breeding strategies. The possibilities of whole genome sequencing at low cost and in a comparably short time have now opened the way for the use of advanced genome analysis tools like quantitative trait loci (QTL) analysis to identify, at least under some conditions, all causative genes for a certain trait [ 32 ] or even several different genetic combinations giving rise to the same phenotype [ 33 ]. Extreme QTL (X-QTL) analysis and intercross QTL (iQTL), which have recently been improved greatly, provide sensitivity and detection of even modest changes in a trait to a single gene or even nucleotide level, simultaneously covering all causal loci contributing to heritability of the trait [ 32 , 34 ].…”
Section: Predicting Improved Robustness and Stress Tolerancementioning
confidence: 99%